Law, Liability, and Ethics for Medical Office Professionals, 6th Edition - Myrtle R. Flight; Wendy Mia Pardew (Cengage Learning, 2017)
Updated to reflect new health care regulations and technology, LAW, LIABILITY, AND ETHICS FOR MEDICAL OFFICE PROFESSIONALS, SIXTH EDITION prepares future medical assistants for the legal and ethical dilemmas they'll face in medical environments. Beginning with business-related issues and the court system, chapters next take readers through the standard of care, employment, criminal and tortious acts, contractual issues, negligence, medical malpractice, and other important matters of law. The second half of the book delves into the ethical concerns present in medical practices, including patient confidentiality, health records, professional ethics, and the issues associated with patient births and deaths. A practical resource for novices and seasoned professionals, the book also offers real-life cases and news stories to ground readers in relevant laws and ethical issues, along with chapter-ending activities to practice their own decision-making skills. Thoughtful and thorough, LAW, LIABILITY, AND ETHICS FOR MEDICAL OFFICE PROFESSIONALS, SIXTH EDITION shows medical assisting students their legal and ethical obligations, when to seek legal advice and how to work with the legal profession, and how to protect themselves and their future employers from medical malpractice and other complaints.